PENGARUH METODE PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMP NEGERI 1 MERANGIN - Yohanes (Pendidikan Matematika | Universitas Merangin, 2016)
This research is motivated by students' low mathematical communication skills. Students have difficulty in solving questions related to mathematical communication. One reason is learning that only uses conventional learning models, so students' creativity and activity are still less visible. The purpose of this study was to find out and describe mathematical communication skills taught by problem based learning learning methods better than those taught with conventional learning models with expository methods. This type of research is a Quantitative Approach with quasi experimental methods. The sample of the study amounted to 67 students, 33 students in the experimental class and 34 students in the control class obtained by the Simple Random Sampling technique. The technique of collecting data through a test of mathematical communication skills in the form of a description sheet (Essay) consisting of 8 questions. The data analysis technique uses the t-test. The results revealed that the results of the average experimental class score were higher than the results of the average score of the mathematical communication skills of the control class students. Thus the problem based learning learning method influences students' mathematical communication skills ( . The conclusion of this study is that mathematical communication skills of students who use problem based learning learning methods are better than students' mathematical communication skills using conventional learning, meaning learning methods of problem based learning provide an influence on mathematical communication skills.